Is Participation in Tourism Market an Opportunity for Everyone? Some Evidence from Italy - Cristina Bernini; Maria Francesca Cracolici (Fondazione Eni Enrico Mattei (FEEM), 2014)
Exploring the main determinants of tourism participation at national and international level, the paper investigates if there are differences in tourism consumption behavior among Italian families which reflect disparities in their standard of living. To achieve this a Heckman model has been used on a huge sample of Italian households over the period 1997-2007. Results show that participation in the tourism market is strongly affected by the personal characteristics of individuals and that tourism consumption is an income sensitive good. The analysis reveals that tourism is generally a luxury good reflecting the disparities in the standard of living among Italian families. We have found that participation in the tourism market is affected not only by economic constraints, but also by cultural and territorial factors.
Keywords: D10; C23; C24; L83; 330; Tourism Consumption; Income Elasticity; Household Characteristics; Domestic and International Travels; Standard of Living